PEMBERDAYAAN ZAKAT DALAM MENINGKATKAN KESEJAHTERAAN UMAT - Andriyanto, Irsyad (UIN Sunan Kudus, 2014)
Zakat should be managed in a productive and professional. Domestic politics haveresulted in Zakat Act No 38/1999, which was then amended by Zakat Act No23/2011. This new Act mandated a stronger integration of zakat managementin the country. According to the Act, the zakat institution is divided in two:(i) government board of zakat and (ii) private zakat institutions. The formeris known as Badan Amil Zakat Nasional (abbreviated as BAZNAS), or theNational Board of Zakat, and the latter is known as Lembaga Amil Zakat(abbreviated as LAZ). BAZNAS was given a mandate to lead the integrationprocess and to coordinate all other zakat institutions comprising BAZNASat the Provincial and City/Regency levels and LAZ. This paper attemptsto discuss policy design and strategic steps that can fully support futuredevelopment of zakat in Indonesia. This study uses socio-economic approach. Theanalysis serves to simplify data into a form that is easier to read and interpret.The analysis used in this research is descriptive analysis.